Prenatally androgenized PCOS mice have ovary-independent uterine dysfunction and placental inflammation aggravated by high-fat diet - Luyckx, Lena; Myllykangas, Milena; Saarela, Ulla; Virtanen, Nikke; Hurskainen, Elisa; Savolainen, Audrey; Ollikainen, Nadja; Norlén, Anna-Karin; Ohlsson, Claes; Poutanen, Matti; Velde, Greetje Vande; Arffman, Riikka K.; et al. (AMER ASSOC ADVANCEMENT SCIENCE, 2025)
Polycystic ovary syndrome (PCOS) is a common hyperandrogenic and metabolic condition in women. The syndrome is linked to subfertility and pregnancy complications, yet the independent effects of exposure to hyperandrogenism and obesity on endometrial function remain unclear. Here, PCOS-like mice were generated using prenatal androgenization (PNA) with dihydrotestosterone, followed by a prepubertal high-fat (HF) or standard diet. In ovariectomized mice, PNA impaired uterine closure during the implantation window, disrupted decidualization, and altered extracellular matrix- and inflammation-related gene expression. The effects were aggravated by the HF diet. In naturally mated, ovary-intact mice, PNA and HF diet affected decidual and placental gene expression, suggestive of placental dysfunction and inflammation, and induced fetal growth restriction. This study underlines the role of the uterus in adverse pregnancy outcomes in PCOS and identifies possible underlying mechanisms for future studies. Prepregnancy interventions targeting metabolic health and hyperandrogenism should be the next steps to optimize PCOS pregnancy outcomes.